Portal vein arterialization for iatrogenic embolization of the hepatic artery. An old but still useful technique?. (2020) - Reese, Tim; von Rittberg, York; Oldhafer, Karl J.
Highlights: A Patient was treated with portal vein arterialization for iatrogenic occlusion of the hepatic artery after pancreatoduodenectomy. Portal vein arterialization is an old surgical method, which could be helpful to reduce the failure-to-rescue rate of patients with a dearterialised liver. Portal vein arterialization is a rare but safe technique to supply arterial blood to the liver. Abstract: Introduction: Portal Vein Arterialization is a rare procedure for total de-arterialized livers to ensure arterial inflow to the liver. Presentation of case: A 55-year-old male patient underwent pancreatoduodenectomy for chronic pancreatitis. One month after discharge the patient was re-admitted because of bleeding from a pseudoaneurysm of the ligated gastroduodenal artery. During radiological intervention a coil dislocated and a complete occlusion of the hepatic artery occurred. Extraction of the coil was not possible, therefore, the patient was transferred to our hospital for surgical revascularization. We performed a side-to-side running anastomosis between a branch of a mesenteric artery and the corresponding vein to supply arterial blood to the liver. The postoperative course was uneventful. Radiologic examinations showed a patent arterio-portal shunt. Discussion: Portal vein arterialization might be a lifesaving procedure in complication management. Conclusion: PVA is an old surgical method, which could be helpful to reduce the failure-to-rescue rate.